2014
DOI: 10.1073/pnas.1318978111
|View full text |Cite
|
Sign up to set email alerts
|

Androgens regulate ovarian follicular development by increasing follicle stimulating hormone receptor and microRNA-125b expression

Abstract: Although androgen excess is considered detrimental to women's health and fertility, global and ovarian granulosa cell-specific androgen-receptor (AR) knockout mouse models have been used to show that androgen actions through ARs are actually necessary for normal ovarian function and female fertility. Here we describe two AR-mediated pathways in granulosa cells that regulate ovarian follicular development and therefore female fertility. First, we show that androgens attenuate follicular atresia through nuclear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
188
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 255 publications
(202 citation statements)
references
References 61 publications
10
188
1
3
Order By: Relevance
“…As the most physiologically important nuclear receptor and cell surface receptor in ovarian follicles, respectively, AR and FSHR are considered to be essential regulators of GC biology (Wang et al 2015). Many recent publications demonstrated that AR and FSHR mRNA levels are tightly correlated (Catteau-Jonard et al 2008, Nielsen et al 2011 and that androgens can regulate FSHR expression in GCs (Sen et al 2014, (I) Luciferase activity assays. miR-126* or NC mimic was co-transfected with pmirGLO-FSHR-3′-UTR mut.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As the most physiologically important nuclear receptor and cell surface receptor in ovarian follicles, respectively, AR and FSHR are considered to be essential regulators of GC biology (Wang et al 2015). Many recent publications demonstrated that AR and FSHR mRNA levels are tightly correlated (Catteau-Jonard et al 2008, Nielsen et al 2011 and that androgens can regulate FSHR expression in GCs (Sen et al 2014, (I) Luciferase activity assays. miR-126* or NC mimic was co-transfected with pmirGLO-FSHR-3′-UTR mut.…”
Section: Discussionmentioning
confidence: 99%
“…Because miR-126* expression is regulated by AR, we postulated that AR regulates FSHR expression via miRNAs. One downstream target of AR is miR-125b, which represses p53 expression; this miRNA cooperates with AR to synergistically inhibit the p53 function in mGCs (Sen et al 2014). Similarly, Ribas et al (2009) showed that androgen-bound AR up-regulates expression of miR-21, and the AR/miR-21 axis exerts oncogenic effects in prostate tumors by down-regulating TGFBR2 (Mishra et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations